Analisis Fungsi Peraturan Mentri Pendidikan, Kebudayaan, Riset dan Teknologi Nomor 30 Tahun 2021 dalam Mencegah Kekerasan Seksusal di Kampus - Andika Suherman; Lina Aryani; Eka Yulyana (Peneliti.net, 2021)
Regulation of the Ministry of Education, Culture, Research and Technology number 30 of 2021 or better known as PPKS is a regulation that was born on the rise of sexual violence on campus. The presence of PPKS invited a fierce and viral debate between the two sides, where the supporters stated that PPKS was the hope in alleviating cases of sexual violence on campus, while the contra called PPKS a controversial regulation because it could legalize free sex on campus. Analysis is needed to examine this problem. This study uses a combination of qualitative and quantitative methods, with samples taken at random to 100 students in 20 different campuses. The results of the research and analysis of the discussion show that philosophically many PPKS rules do not conflict with the Pancasila philosophy and the 1945 Constitution, sociologically PPKS gets a lot of support in academic circles but rejection among religious groups and juridically still found formal and material defects in the drafting process PPKS